Offspring's labor migration and its implications for elderly parents' emotional wellbeing in Indonesia. (May 2021) - Kumar, Sneha
Abstract: Population ageing and labor out-migration are increasingly challenging normative intergenerational support systems and familial welfare in parts of Asia. Extant studies look at how migration affects the material wellbeing of sending-households, but less is known about how migration shapes the emotional health of non-migrants as origin and destination conditions evolve. This study examines how labor migration among adult children shape the emotional health of elderly parents in Indonesia, and how observed implications are modified by alternative care arrangements and different migrant destinations. Using panel data from 2101 respondents age 50+ in the 2007 and 2014 Indonesia Family Life Survey, and individual-level fixed effects regressions, this study finds that offspring's migration is associated with increased parental depression, net of covariates. Depressive outcomes are abated if resulting care deficits are offset by co-residence or daily interactions with adult children, or if children move to economically lucrative international destinations; however, having a child in Malaysia – a destination characterized by high informal labor employment – increased parental depression. These findings draw attention to the non-economic implications of migration and the distress experienced specifically by parents who lack intergenerational support and who have concerns about child's wellbeing at destination. Highlights: Adult child's labor migration increases depression for elderly parents left behind. Non-migrant parent's distress increases net of improvements in economic status. Non-migrant parent's distress is heightened if they lack family support. Non-migrant parent's distress is heightened if children do precarious work. Study highlights heterogeneities in the experiences of migrant-sending homes.